EVALUASI PERENCANAAN KELISTRIKAN - Zalmadi Syamsudin; Andi Makkulau; Lutfian Nizar (Sekolah Tinggi Teknik - PLN, 2016)
So that the operation of the electric power system to be efficient, we need a plan development of a proper electricity.physical development planning electricity reference West Kalimantan on RUPTL. This research discusses electricity planning West Kalimantan with an overview of the technical spesifications of the system, both on the generation and transmission side, to the side of generation is implemented based screening curve, to the transmission side evaluation is carried out using the specifications of the existing system in Java